STUDENT ORGANIZATIONS AS NON-FORMAL EDUCATIONAL SPACES IN STRENGTHENING STUDENTS' PANCASILA MORAL CHARACTER: A SYSTEMATIC LITERATURE REVIEW - Annisa Muharromah; Dadang Sundawa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the role of student organizations in strengthening Pancasila moral values ​​through a Systematic Literature Review (SLR) approach. The SLR method was applied, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A literature search was conducted through the Google Scholar and Garuda databases for journal articles published between 2021 and 2025. Based on inclusion and exclusion criteria, 11 articles were selected for systematic analysis. The results of this study indicate that student organizations play a significant role in strengthening Pancasila moral character through learning and training in experience-based organizational activities, cadre development, leadership, deliberation, and student social interaction. Furthermore, it was found that active student involvement in these organizations is a crucial driving factor in maintaining the effectiveness of student organizations, which impacts students' Pancasila moral awareness. Therefore, this study addresses new facts regarding the role of student organizations as strategic non-formal educational spaces in strengthening students' Pancasila moral character.